Bioactive glucosinolates and antioxidant properties of broccoli seeds cultivated in Thailand - Sarunya Chuanphongpanich (2018)
One of the most significant health concerns of cruciferous vegetables is the presence of biologically active compounds, glucosinolates. Broccoli (Brassica oleracea var. italica) is a nutritionally important crop grown all over the world. Glucosinolates have been found to have anti-cancer properties. The primary purpose of this study was to evaluate glucosinolate content and antioxidant property in the seeds of broccoli cultivars widely grown in Thailand. Glucosinolates were analyzed with high performance liquid chromatography (HPLC). Total and individual glucosinolate levels varied significantly among cultivars. In all broccoli seeds, 4- methylsulfinylbutylglucosinolate (glucoraphanin) was the predominant glucosinolate. The highest total glucosinolates was 65.5 μmol/g DW in 'Top Green #067' cultivar, followed by 'Packman' (58.6), 'Green Queen' (51.2), 'Pak Ging' (25.5) and 'Rod Fai' (20.3). The antioxidant capacities, including ABTS radical scavenging activity and ferrous ion chelating ability in the methanol and water extracts, were found to be high.